Alkynyl Moiety for Triggering 1, 2‐Metallate Shifts: Enantiospecific sp2–sp3 Coupling of Boronic Esters with p‐Arylacetylenes. Issue 33 (12th July 2017) - Ganesh, Venkataraman; Odachowski, Marcin; Aggarwal, Varinder K.
Abstract: The enantiospecific coupling of secondary and tertiary boronic esters to aromatics has been investigated. Using p‐lithiated phenylacetylenes and a range of boronic esters coupling has been achieved by the addition of N‐bromosuccinimide (NBS). The alkyne functionality of the intermediate boronate complex reacts with NBS triggering the 1, 2‐migration of the group on boron to carbon giving a dearomatized bromoallene intermediate. At this point elimination and rearomatization occurs with neopentyl boronic esters, giving the coupled products. However, using pinacol boronic esters, the boron moiety migrates to the adjacent carbon resulting in formation of ortho boron‐incorporated coupled products. The synthetic utility of the boron incorporated product has been demonstrated by orthogonal transformation of both the alkyne and boronic ester functionalities. Abstract : Find your way : The enantiospecific coupling of secondary and tertiary boronic esters to p ‐arylacetylenes has been achieved by the addition of N ‐bromosuccinimide. By tuning the steric environment around boron, the coupled product with or without boron can be targeted. The boron‐containing product is highly versatile, as each functional group can be transformed chemoselectively.